A case of left ovarian vein thrombosis. (18th April 2012) - Tailor, V; Jaspal, R; Wahba, J; Joash, K
Abstract : Background: Venous thromboembolic events are the main cause of direct maternal deaths in the UK, of which pelvic ovarian vein thrombosis (POVT) is a relatively uncommon manifestation with an incidence of 0.02% - 0.05% in post partum women. We present a case report of a left POVT with an overview of the current literature. Case Report: A 32 year old, multiparous lady, presented four days after an uncomplicated vaginal delivery with severe left sided abdominal pain radiating down the thigh. Associated signs included pyrexia, tachycardia, and elevated inflammatory markers. Initially treated as sepsis secondary to endometritis or pyelonephritis, the diagnosis of POVT extending to the renal confluence was made following CT imaging. Initial treatment with broad spectrum antibiotics and prophylactic low molecular weight heparin was modified after blood cultures confirmed growth of Staphylococcus aureus . Oral flucloxacillin was given and six month treatment with oral anti-coagulation with warfarin was commenced. The patients symptoms were much improved after 3 days of treatment, with a delay in discharge due to warfarin sensitivity. Discussion: Because POVT occurs on right side in 80-90% of cases, diagnosis of left POVT may be delayed leaving patients at risk of developing serious sequelae. Reports of positive blood cultures, as in this case, or thomboembolism cultures suggest an infectious aetiology and therefore antibiotics with anti-coagulation forms the mainstay of treatment. Conclusion: Left POVT should be considered when post-partum abdominal pain presents with atypical features including radiation to the thigh, pyrexia and leucocytosis.